VARIATION OF THE HERITABILITY OF BALI CATTLE WEIGHT ATBALAI PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BPTU-HPT) DENPASAR - H., Setiawan; Warmadewi, D. A.; Oka, I G. L. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
Heritability is one of the genetic parameters which is requiredforselection. It is influenced by genotipic and phenotipic variations. Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Denpasar is goverment institution which is responsible to do breeding program in Indonesia.The purpose of this study was to find out the variation of heritability values of birth, weaning, and yearling weight of Bali cattle in BPTU-HPT Denpasar from 2012 to 2015. Model applied to predict the heritability value in this study was "Unequal numbers of progeny per sire"(Becker, 1985). The data used in this study was birth,weaning, and yearling weight data from 2012 to 2015.Data was  analyzed with SPSS 24.0. In addition, heritability value was calculated with h 2 = 4? 2 s/? 2 s+? 2 w (Becker, 1984) formula. The results showed that the heritability of birth, weaning and yearling weight were vary from negative to positive. Negative value due to less number of bull used inthe population. Keywords: Bali Cattle, Heritability, Body Weight